Patogenia do Vaccinia Virus GP2 em bovinos - Anselmo Vasconcelos Rivetti Junior (2012)
Bovine vaccinia (BV) is a zoonosis caused by Vaccinia virus (VACV), which affects dairy cattle and milkers, and causing economical, animal and human health impacts. By the clinical presentation of the disease, it seems that BV is a localized disease, with lesions restricted to the skin of affected individuals. But there are no studies about the pathogenesis of the disease in cows to access if there is a systemic spread of the virus and if there are different ways of VACV shedding. This work had the objective to study if occurs viremia and VACV shedding in the feces of VACV experimentally infected cows. To this end, ten crossbred lactating cows, serologically negative for VACV, were used. Three teats of each cow were scarified using sandpaper, followed by inoculation of 106 UFP/50µL of Guarani P2 (GP2V) strain of VACV. All animals were monitored daily and blood and feces samples were collected for 67 days post infection (d.p.i.). After this period, all animals that were previously infected were divided in two treatment groups: re-infection or immunodeppression. All animals developed lesions compatible with VB (papules, vesicles and ulcers), and even after the resolution of the lesions, viral DNA was detected in the blood and lymphoid tissues, as well as an intermittent and extended detection of VACV DNA in the feces, until the last day of collection (67 day post infection), suggesting that VACV infection is chronic. The detection of VACV viable particles in the feces suggests that this is a possible route of viral shedding in the environment, which may favor VACV transmission within and among properties. VACV infections in cattle are associated with infection of epithelial cells and goblet cells in the intestine, and macrophages and lymphocytes in lymphoid tissues. In the animals experimentally infected and then immunodepression, VACV DNAnemia and DNA detection in feces were observed even before the immunodepressive treatment. There was a tendency to an increase in DNA detection in the blood and feces after the treatment, suggesting that there is some mechanism of VACV persistent infection in cattle and that this is influenced by the immune system. The group of animals that were reinfected by VACV, presented lesions in the teats once more, and VACV DNAnemia was observed. This study showed new evidence that VACV infection in cattle is systemic, has a chronic course and that there is viral shedding on the feces.